Correction to: Is digital twin a better solution to improve ESG evaluation for vaccine logistics supply chain: an evolutionary game analysis (Operations Management Research, (2023), 16, 4, (1791-1813), 10.1007/s12063-023-00385-w) - Zhang M.; Yang W.; Zhao Z.; Pratap S.; Wu W.; Huang G.Q. (My University, 2025)
In this article the wrong figure appeared as Fig. 1.; the figure should have appeared as shown below. The original article has been corrected. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.